Mind wandering and the attention network system - Gonçalves, Óscar F. (2017)
Attention and mind wandering are often seen as anticorrelated. However, both attention and mind wandering are multi-component processes, and their relationship may be more complex than previously thought. In this study, we tested the interference of different types of thoughts as measured by a Thought Identification Task TIT (on task thoughts, task related interference thoughts, external distractions, stimulus independent and task unrelated thoughts) on different components of the attention network system - ANT (alerting, orienting, executive). Results show that, during the ANT, individuals were predominantly involved in task related interference thoughts which, along with external distractors, significantly impaired their performance accuracy. However, mind wandering (i.e., stimulus independent and task unrelated thoughts) did not significantly interfere with accuracy in the ANT. No significant relationship was found between type of thoughts and alerting, orienting, or executive effects in the ANT. While task related interference thoughts and external distractions seemed to impair performance on the attention task, mind wandering was still compatible with satisfactory performance in the ANT. The present results confirmed the importance of differentiating type of "out of task" thoughts in studying the relationship between though distractors and attention.